2010
DOI: 10.1590/s0104-92242010000300010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the heat input in the mechanical integrity of the welding joints welded by GMAW and LBW process in Transformation Induced Plasticity steel (TRIP) used in the automotive industry

Abstract: ResumoNeste trabalho, uma chapa de aço de alta resistência (AHSS -Advanced High Strength Steel) tipo TRIP (Transformation Induced Plasticity) empregado atualmente no setor automotivo foi soldado usando o processo de soldagem a arco com arame solido sob proteção gasosa (GMAW) e soldagem com LASER de CO 2 (LBW). As propriedades mecânicas das amostras soldadas quanto a tração e microdureza foram determinadas e os resultados foram relacionados com as microestruturas apresentadas. Verificou-se que a solda com LBW c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 1 publication
0
3
0
2
Order By: Relevance
“…Zhang et al [28] used GMAW to weld a TRIP600 (ferrite, retained austenite and bainite BM) and showed that the weld exhibited excellent mechanical and impact properties due to the microstructural make-up of the fine grained HAZ, which consisted of ferrite and granular bainite. Lopez Cortez et al [29] also found that the HAZ of a GMAW welded TRIP800 automotive steel consisted of a mixed ferrite (polygonal) and bainite (lower), while the fusion zone consisted of martensite and some ferrite (Widmanstatten and allotriophic) and bainite (upper). Grachar et al [30] laser welded an automotive TRIP (ferrite with bainite-austenite BM) and revealed that the microstructure within the inter-critical HAZ (ICHAZ) consisted of ferrite and areas consisting of lath bainite-martensite-austenite.…”
Section: Welding Of Trip Steelsmentioning
confidence: 93%
“…Zhang et al [28] used GMAW to weld a TRIP600 (ferrite, retained austenite and bainite BM) and showed that the weld exhibited excellent mechanical and impact properties due to the microstructural make-up of the fine grained HAZ, which consisted of ferrite and granular bainite. Lopez Cortez et al [29] also found that the HAZ of a GMAW welded TRIP800 automotive steel consisted of a mixed ferrite (polygonal) and bainite (lower), while the fusion zone consisted of martensite and some ferrite (Widmanstatten and allotriophic) and bainite (upper). Grachar et al [30] laser welded an automotive TRIP (ferrite with bainite-austenite BM) and revealed that the microstructure within the inter-critical HAZ (ICHAZ) consisted of ferrite and areas consisting of lath bainite-martensite-austenite.…”
Section: Welding Of Trip Steelsmentioning
confidence: 93%
“…Mujica et al [2,3] and López Cortéz et al [4] reported martensite formation in FZ and HAZ of Transformation Plasticity (TRIP) steels after laser welding. The hardness typically attains 500 HV in these cases, thus rendering the weldment very brittle for post-processing.…”
Section: Formability Of In-situ Austempered Transformation-induced Plasticity Steels After Laser Beam Weldingmentioning
confidence: 99%
“…There are studies in the literature reporting the weldability and post-weld strength values of DP steels and TRIP steels with welding methods such as gas metal arc welding (GMAW) [13,14], laser beam welding (LBW) [15,16] and resistance spot welding (RSW) [17,18]. There is some studies about advanced high strength steels are used at automotive industry welded by EBW [19][20][21].…”
Section: Introductionmentioning
confidence: 99%